Acidentes de trânsito com envolvimento de motociclistas: Uberlândia 2002 a 2004 - Silva, Rejane Maria da (2007)
Currently, in Brazil, the traffic accidents kill nearly 30.000 people and another quantity is wounded every year. This situation is a serious problem for the society and the authorities. In this context, we observed the motorcycles are addicted on the fleet of vehicles in increasing number because it is a particular vehicle with relative easiness of purchase, economy and for satisfying to the necessity of a public. However the increase of motorcycles fleet in the cities road system has generated conflicts between the conductors; so it leads to the occurrence of traffic accidents that generally causes wounds to the victims or deaths, since the motorcycle is a vehicle without enough protection to the users. In Uberlândia the traffic accidents problem is also evident. Therefore the objective of this dissertation is to know and to characterize the motorcycles traffic accidents occurred in the period between 2002 and 2004, at the city. The local reality knowledge on the traffic accidents is the first step to reduce the number of victims. In this way, with data of the Occurrence Reports, it was evidenced that 26.06% of TA in Uberlândia involves motorcycle drivers. However, as the DATASUS, the motorcycle drivers represent 45% of the accident victims who need medical internments and 35.24% of the deaths provoked by traffic accidents. According the Occurrence Reports, the DATASUS and the Medical Legal Post, between the traffic accident victims on motorcycles, more than 80% of them are men, and the age of more involvement in accident is the young who are 20 to 29 years old. Beyond the great use of motorcycle as individual transport for diverse reasons (work, school, leisure), it still serves as work instrument for professionals (office boys and mototaxi pilots). Thus the motorcycle is a form of job and even the way for many people ingress in the work market. In the activities of delivery and transport of passengers, the office boys and mototaxi pilots workers are displayed for some hours to the transit under great risk of accidents. In a preliminary research, we evidenced that 61% of the mototaxi pilots works between 9 and 12 daily hours. About the office boys, 66% work up until eight hours a day/ however, 28% work 9 to 12 hours. The research indicated that 50% of the office boys and 74% of the mototaxis pilot workers already had been involved in traffic accidents. On the professionals already involved in traffic accidents, nearly 56% of the office boys and 58% of the mototaxis pilots workers already had been involved in accident for more than two times. This study presents the joint necessity of actions to reduce the number of victims in the traffic. Between them, the agencies integration of the information that deal with this subject in an only local (Data Base) to have a faster reply on the knowledge and characterization of the accidents, making possible actions of short, medium and long term. The training of military policemen, transit agents and firemen is necessary for these professionals have cares in the confection of Occurrence Report that are essentials to collect information about accidents; the training of the professionals responsible for the maintenance of the Data base this way, inconsistencies don t occur and don t difficult the analysis of the information; finally, the awareness of the professionals of the hospitals and the Legal Medical Rank fat they identify if the patients are victims of traffic accidents. The identification of the critical points and the accidents victims serves as subsidy to the short-term treatment of the places where there is the most occurrences of accidents, and medium and long term to all system. Beyond, it assists the permanent education for the traffic campaigns destined to all, but mainly focused on the moto drivers and professional pilots, remembering the importance of the inspecting.